Examining the epoxidation process of soybean oil by peracetic acid - Nykulyshyn, Irena; Pikh, Zorian; Shevchuk, Liliya; Melnyk, Stepan (Eastern-European Journal of Enterprise Technologies, 2017)
The main principle of green chemistry is the use of renewable, ecological raw materials, which will contribute to subsequent biodegradation and reduction of toxicity of the product in the production of polymers. Vegetable oil (VO) is the cheapest and most common biological raw material, the use of which has such advantages as low toxicity and natural biodegradation. We analyzed experimental dependences of the consumption of reagents and the accumulation of epoxide in the interaction between a solution of soybean oil (SO) in toluene and the epoxidizing systems H2O2/acetic acid (AA)/KU-2´8 and H2O2/acetic anhydride (AAn)/KU-2´8. It was established that the use in the process of epoxidation of soybean oil of the specified systems makes it possible to achieve high values of selectivity of epoxidation by double bonds. The resulting values of selectivities in the epoxidation process by double bonds and by the consumption of peroxide when studying the epoxidizing system Н2О2/AAn/KU-2´8 are higher. The advantages of using the specified epoxidizing system include a reduction in the total volume and mass of the reaction mixture. Obtaining the epoxidized soybean oil with a low resulting value of bromine number provides subsequent good thermal and oxidative stability of materials on its base. We calculated the values of rate constants of the epoxidation reaction of SO at different temperatures. By using the methods of IR and Raman spectroscopic studies, we demonstrated structural changes in raw materials and confirmed the progress of the epoxidation reaction. The developed technique for recalculating the values of bromine, iodine numbers of products of the epoxidation reaction, unsaturation and epoxy number, selectivity of the process in the epoxidation of mixtures of unsaturated compounds allows comparing the results of research. The use of the specified technique also makes it possible to draw unambiguous comparative conclusions about the effectiveness of reagents consumption and the selectivity of reaction. In this case, there is a possibility to improve the technology of obtaining the epoxidized compounds. The calculation formulas obtained were applied to analyze the progress of the epoxidation process of soybean oil.